Seafood Perceptions among People Aged 55 and Above: Summary of Focus Groups Results: FE821/FE821, 11/2009 - Wysocki, Allen F.; House, Lisa; Messina , William A. (EDIS, 2009)
FE821, a 5-page fact sheet by Allen F. Wysocki, Lisa House, and William A. Messina, Jr., provides a brief summary of the focus group part of a study of perceptions of Florida residents aged 55 and over on seafood consumption. Published by the UF Department of Food and Resource Economics, November 2009. Reviewed March 2013. FE821/FE821: Seafood Perceptions among People Aged 55 and Above: Summary of Focus Groups Results (ufl.edu)